(untitled) (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2022)
The study aims to determine the effect of reading comprehension skills and language attitudes on the summary writing skills of fourth grade students at SD Negerei Panaikang 2 Makassar. The type of research used was descriptive quantitative with ex post facto design. The population in this study were all fourth grade students of SD Negeri Panaikang 2 Makassar as many as 80 students. Sampling was done randomly so that a sample of 30 grade IV students of SD Negeri Panaikang 2 Makassar was obtained. The data were analyzed by using the SPSS application to perform normality test data, multicollinearity test, heteroxidity test, partial t test, and simultaneous F test. The result of the study obtained an average value of reading comprehension ability which was 76.83. Regarding the language attitudes, students got an average value of 78.6933. The students summary writing skills got an average score of 74.19. In the inferential statistical test of the sig. value, the ability of reading comprehension on summary writing skills was 0,001 < 0,05 and language attitudes towards summary writing skills was 0,040 < 0,05, showing that the X1 variable had an effect on the variable and the X2 variable had an effect on Y. The result of the simultaneous F test resulted in a significant value of 0,000 < 0,05 stating that the ability of reading comprehension and language attitudes had a significant effect on the summary writing skills of fourth grade students at State Elementary School Panaikang 2 Makassar.